The Role Of Wearable Devices Technology In Monitoring Heart Health In The Elderly In Indonesia - Sumiyati Sumiyati (Al Makki Publisher, 2025)
Cardiovascular disease is still the leading cause of death in the world, including in Indonesia, with an increasing prevalence in the elderly. Limited access to health services, low digital literacy, and limited medical personnel in rural areas add to the complexity of heart health problems. This study aims to explore the role of wearable devices technology in monitoring heart health in the elderly in Indonesia. The research method uses a qualitative approach with a case study design. The research subjects consisted of 12 elderly people aged 60–75 years, 5 family members, and 3 health workers in the city of Bandung and Cirebon Regency. Data were collected through in-depth interviews, participatory observations, simple questionnaires, and documentation studies. The results of the study show that the majority of the elderly consider wearable devices useful in early detection of heart symptoms, increasing health awareness, and providing a sense of security for families. The main obstacles identified include low digital literacy (42%), device costs (33%), and inconvenience of use (25%). Seniors who live with their families are more compliant with devices than those who live alone. This study confirms that the effectiveness of wearable devices is influenced by social, economic, and cultural factors. With the support of families, health workers, and inclusive public policies, this technology has the potential to strengthen the digital transformation of elderly health services in Indonesia.